2002
DOI: 10.1046/j.1365-2958.2002.03204.x
|View full text |Cite
|
Sign up to set email alerts
|

The Salmonella enterica sv. Typhimurium smvA, yddG and ompD (porin) genes are required for the efficient efflux of methyl viologen

Abstract: SummaryIn Gram-negative bacteria, a subset of inner membrane proteins in the major facilitator superfamily (MFS) acts as efflux pumps to decrease the intracellular concentrations of multiple toxic substrates and confers multidrug resistance. The Salmonella enterica sv. Typhimurium smvA gene encodes a product predicted to be an MFS protein most similar to QacA of Staphylococcus aureus . Like mutations in qacA , mutations in smvA confer increased sensitivity to methyl viologen (MV). Mutations in the adjacent omp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(71 citation statements)
references
References 42 publications
6
63
0
Order By: Relevance
“…Interestingly, the synthesis of this porin is dependent on cyclic AMP (B. Rotman and G. F.-L. Ames, personal communication). The gene ompD is located downstream of the putative transporter gene yddG, and recently the inactivation of either of these genes was reported to cause hypersusceptibility to methyl viologen (577). The authors propose that the OmpD porin forms a multiprotein complex with the YddG pump, playing the role of the exit channel like TolC.…”
Section: Other Porinsmentioning
confidence: 99%
“…Interestingly, the synthesis of this porin is dependent on cyclic AMP (B. Rotman and G. F.-L. Ames, personal communication). The gene ompD is located downstream of the putative transporter gene yddG, and recently the inactivation of either of these genes was reported to cause hypersusceptibility to methyl viologen (577). The authors propose that the OmpD porin forms a multiprotein complex with the YddG pump, playing the role of the exit channel like TolC.…”
Section: Other Porinsmentioning
confidence: 99%
“…It has been reported that SmvA is involved in resistance against methyl viologen 23) and acriflavine. 24) We cloned the smvA gene, introduced it into cells of the drug-hypersusceptible E. coli KAM32 host, and measured the MICs of various antimicrobial agents. E. coli KAM32/pSMVA3 (carrying smvA) showed elevated MICs of tetracycline, norfloxacin, acriflavine, ethidium bromide, methyl viologen, TPPCl and so on, compared with E. coli KAM32/pSTV28 (control) ( Table 1).…”
Section: Changes In Mics Of Drugs Due To Kmra or Smvamentioning
confidence: 99%
“…Thus, it is clear that KmrA belongs to the multidrug efflux pumps of the MF superfamily. 24) Proteins or hypothetical proteins that showed sequence similarity with KmrA are widely distributed in both Gram-negative and Gram-positive bacteria (Swiss-Prot database) including Erwinia, Pseudomonas, Streptococcus, Streptomyces, Mycobacterium, Nocardia and Corynebacterium. Among these bacterial genera, it seemed that many similar proteins (or hypothetical proteins) are present in Streptomyces (data not shown).…”
Section: Changes In Mics Of Drugs Due To Kmra or Smvamentioning
confidence: 99%
“…We have demonstrated that a M null mutant is more sensitive to a subfamily of superoxide-generating reagents related to PQ but not to other superoxide generators such as mena- (39). SmvA is similar to the MvrA protein of E. coli (17,29).…”
Section: Discussionmentioning
confidence: 89%